Applying Situational Teaching to Enhance Emergency Language Skills - Zhu, An; Chen, Peng-Fei (Educational Researcher Journal, 2025)
This study aims to examine the effectiveness of the Situational Teaching method in enhancing emergency language skills among foreign language learners, particularly in the context of using English as a communication tool during crisis or emergency situations. Emergency language skills are increasingly essential in today’s global landscape, especially for individuals working in fields such as healthcare, tourism, transportation, or disaster response, where clear and rapid communication is critical. A quasi-experimental method was employed using a pre-test and post-test control group design. The study involved 60 intermediate-level language learners who were randomly assigned to two groups: an experimental group that received instruction through Situational Teaching, and a control group that was taught using conventional grammar-based methods. Data collection instruments included emergency language proficiency tests, classroom observations, and semi-structured interviews. The instructional program was implemented over eight weeks with two sessions per week. The results revealed a statistically significant improvement (p < 0.01) in emergency language skills scores in the experimental group compared to the control group. Additionally, classroom observations and interviews indicated that learners in the experimental group demonstrated enhanced confidence, fluency, and the ability to comprehend and respond more appropriately and contextually to emergency scenarios. The use of realistic situational simulations was found to increase both emotional and cognitive engagement, which in turn strengthened language acquisition in high-stress contexts. In conclusion, this study affirms that the application of Situational Teaching effectively enhances emergency language skills. It is recommended as a pedagogical strategy within foreign language curricula, especially when addressing the contextual and functional needs of learners in high-pressure environments.